1995
DOI: 10.1111/j.1476-5381.1995.tb16386.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H1 receptor occupancy in human brains after single oral doses of histamine H1 antagonists measured by positron emission tomography

Abstract: 4 There was no correlation between HI receptor occupancy by terfenadine and the plasma concentration of the active acid metabolite of terfenadine in each subject.5 PET data on human brain were essentially compatible with those on HI receptor occupancy in guinea-pig brain determined by in vivo binding techniques, although for the same HI receptor occupancy the dose was less in human subjects than in guinea-pigs.6 The PET studies demonstrated the usefulness of measuring HI receptor occupancy with classical and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 30 publications
(46 reference statements)
4
109
0
2
Order By: Relevance
“…Position emission tomography scans have been found to be useful in the quantitative assessment of sedation caused by firstand second-generation antihistamines. It has been reported that chlorpheniramine occupied 76.8 Ϯ 4.2% of the available H1 receptors in the frontal cortex after a single oral dose of 2 mg, 31 whereas a single dose of cetirizine 20 mg occupied 20% to 50%. 32 However, these studies were done in adults.…”
Section: E118mentioning
confidence: 99%
See 1 more Smart Citation
“…Position emission tomography scans have been found to be useful in the quantitative assessment of sedation caused by firstand second-generation antihistamines. It has been reported that chlorpheniramine occupied 76.8 Ϯ 4.2% of the available H1 receptors in the frontal cortex after a single oral dose of 2 mg, 31 whereas a single dose of cetirizine 20 mg occupied 20% to 50%. 32 However, these studies were done in adults.…”
Section: E118mentioning
confidence: 99%
“…Central H1-receptor occupancy increased significantly with increasing plasma concentration of chlorpheniramine but not with increasing concentration of the active metabolite of ebastine 39 or terfenadine. 31 We know of no such studies with cetirizine.…”
Section: E118mentioning
confidence: 99%
“…The averaged arterial blood concentration was used to calculate the values of the binding potential (BP=Bmax/K d ) of doxepin for available brain H 1 -receptors in each subject as reported previously [4,20]. Parametric neuroimages which present the volume of distribution (V d ) for [ 11 C]-doxepin were generated by graphical analysis [4,21].…”
Section: Image Analysismentioning
confidence: 99%
“…Furthermore, this technology has been applied to a direct in vivo measurement of drug effectiveness in humans, highlighting the essential information needed in the fields of drug development including pharmacology, toxicology, gene targeting, and pharmaceuticals. [2][3][4][5][6][7][8] In recent years, by exploiting new detection technologies, several high-resolution PET and SPECT systems have been developed for imaging the biodistribution of a radiolabeled molecule in small laboratory animals. [5][6][7][8][9] These devices permit noninvasive and repetitive imaging of both the temporal and the spatial biodistribution in a single living animal.…”
Section: Introductionmentioning
confidence: 99%